Jangkaan masa depan kurikulum perubatan herba Orang Asli - Mohd Said, A.; Abdul Rahman, M.N.; Alias, N.; Siraj, Saedah (2014)
The Orang Asli community has its own, such as the work of art, dance moves, music, herbal medicine and storytellers story of faith and the life. This aspect is referred as the indigenous intellectualism and is increasingly marginalized in today's modernization . This paper will highlight the concept of indigenous intellectualism herbal medicine and the importance of education of Aboriginal children . The purpose of this study is to develop a conceptual framework based on curriculum model of intellectualism Aboriginal herbal medicine.. It is a form of alternative approaches in order to uphold intellectualism Aboriginal herbal medicine and further strengthen the identities of Aboriginal generation. In conclusion, Indigenous intellectualism can be maintained through teaching and learning approaches meets the aspirations of Aboriginal who defend their indigenous intellectualism, family values, traditions, beliefs and culture of indigenous peoples from being eroded by the mainstream education system .